Does ESG Disclosure Matter? The Moderating Role of Leverage - Fatimah Sariri; Ika Permatasari; Lintang Venusita (EQUITY, 2026)
The studies look at how sharing ESG information influences a company's cost of capital and how the level of debt in the company affects this cost. This research uses data from companies that are listed on the Indonesian stock exchange for the years 2021 through 2024. This study looks at the total cost of capital, which has two parts: how it affects the cost of debt and how it affects the cost of equity. The study shows that sharing ESG information helps lower the overall cost of capital by reducing the cost of equity, but it did not affect the cost of debt. Moreover, the test results show that ESG has a conditional effect on the cost of capital, meaning its impact is less noticeable when the level of debt is high. For companies that don't have much debt, some ESG disclosures can make a bigger difference in how much it costs them to get capital.But for companies with a lot of debt, the financial risk is more important, and ESG factors don't matter as much to investors. This study adds to what we already know by showing that sharing ESG information doesn't always lead to a lower cost of capital for a company.Instead, it can act as a boundary condition in this relationship. It also shows that investors and creditors in emerging markets react differently to this kind of information.